Local elections results in Ukraine: the authorities reframing - S. S. Zhiltsov (Проблемы постсоветского пространства)
The local elections results in Ukraine, taken place in October 2020, recorded changes in the main political forces alignment. The pro-presidential «Servant of the People» party has lost the electorate support. This further weakened the Ukrainian President Volodymyr Zelensky standings. At the same time, during the local elections, the popular classes supported the pro-Eu-ropean party of the former President Petro Poroshenko. His political party “European Solidarity” managed to gain a significant number of votes in regional and city councils in almost all Ukraine territorial entities. The «Opposition Platform — For Life» party, oriented towards the South-East Ukrainian electorate, received a high level of support. A distinctive feature of the local elections was the voters’ interest decline in radical nationalist parties. The results of local elections reflected changes in the voters mood. The key factor was the economic problems which the Ukrainian authorities faced. As a result, the President of Ukraine and his political party have lost support among the population, which in the future will increase the rivalry between the official Kiev and regional authorities.